A preventive conservation approach for historical timber roof structures. Issue 2 (8th May 2018) - Van Roy, Nathalie; Verstrynge, Els; van Balen, Koenraad
Abstract : Purpose: The purpose of this paper is to illustrate the assets of a preventive conservation approach for historical timber roof structures, as a means to improve the quality and durability of maintenance and repair interventions. Design/methodology/approach: The advantages of a preventive approach for historical structures were identified based on two analyses: a study of the structures' behaviour and an investigation of existing approaches in current practice. The two main identified advantages of the approach, the cyclic process-approach and the potential of knowledge enhancement, were hereafter conceptually implemented in existing approaches. Findings: Current practices focus on single curative interventions, and monitoring is often considered redundant. The importance of monitoring and knowledge enhancement is demonstrated based on the theory of complex adaptive systems (CAS). A preventive conservation approach for historic timber roof structures allows integrating these insights. Research limitations/implications: The analysis of current practice is a sample survey, and the proposed preventive conservation approach is presented at a conceptual level. Future research foresees a more elaborated study of current practice and detailed validation of the developed approach. Originality/value: Three new contributions to the existing research on preventive conservation are: arguments for the implementation of a preventive approach, based on an analysis of the structures' behaviour; the identification of limitations of current approaches that can be tackled in a preventive conservation approach; and the integration of the existing international guidelines and the principles of preventive conservation into a conceptual approach for the monitoring and management of these structures. Furthermore, the research paper demonstrates how timber structures can be understood as CAS, which is a novel viewpoint.